2016
DOI: 10.17759/exppsy.2016090202
|View full text |Cite
|
Sign up to set email alerts
|

Differences of the brain activity in individual, competitive and cooperative behavior between subjects with analytic and holistic cognitive styles

Abstract: Целью исследования было выявление особенностей системной организации поведения у субъек-тов с аналитическим и холистическим когнитивными стилями в процессе индивидуального и группо-вого выполнения задачи выбора при разных формах социального взаимодействия. Предполагалось, что разные формы социального взаимодействия и разные типы ментальности (холистический и ана-литический когнитивные стили) окажутся связанными. Участники исследования (n = 78) вовлека-*Апанович В. В. Магистрант, Государственный академический у… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…We have demonstrated that the systemic organization of behavior associated with competitive and cooperative forms of social interaction is different for subjects with analytical and holistic thinking. It turned out, that the holistic subjects expressed greater sensitivity to different forms of social interaction [45,46]. It is revealed that for subjects with analytical thinking the process of actualization of systems within the subject of behavior state goes CC BY 4.0 ПСИХОФИЗИОЛОГИЯ on faster in competitive forms of interaction, and for subjects with holistic thinking -in cooperative ones.…”
Section: Holistic and Analytic Nature Of Thinking As A Culturally Spementioning
confidence: 99%
“…We have demonstrated that the systemic organization of behavior associated with competitive and cooperative forms of social interaction is different for subjects with analytical and holistic thinking. It turned out, that the holistic subjects expressed greater sensitivity to different forms of social interaction [45,46]. It is revealed that for subjects with analytical thinking the process of actualization of systems within the subject of behavior state goes CC BY 4.0 ПСИХОФИЗИОЛОГИЯ on faster in competitive forms of interaction, and for subjects with holistic thinking -in cooperative ones.…”
Section: Holistic and Analytic Nature Of Thinking As A Culturally Spementioning
confidence: 99%
“…They employed functional magnetic resonance imaging (fMRI) to capture brain activity simultaneously from two subjects in different laboratories with synchronized setups. Since then, advancements in intricate instrumental recording methods and data processing algorithms have led to a growing number of studies analyzing interrelationships in brain region activity and somatovegetative indicators in people during collaborative activities [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The characterization of the collaborative dimension of the activities and the link with job performance was considered in the present study both from individual and collective standpoint but the subjects' psychological characteristics were not addressed. Recent studies undertaken within Professor Alexandrov's team (Apanovich et al, 2016) showed that performance in collaborative activity was sensitive to the holist or analytic character of subjects. Their conclusions suggested that not having taken into account this cognitive aspect might limit the generalization of the result of the present study.…”
Section: Limitationsmentioning
confidence: 99%